Model of correlation between geometry of thermoelectric branches and reliability indicators of single-stage coolers in Q0max mode - Zaikov, V. P.; Meshcheryakov, V. M.; Zhuravlev, Yu. I. (Technology and design in electronic equipment, 2016)
The authors consider the influence of the geometry of thermoelectric branches on the performance reliability of single-stage thermoelectric devices (TED) operating at maximum cooling capacity at 2.0 W thermal load for any values of temperature difference (from 10 to 60 K). A model of correlation of these parameters is presented. It is shown that when the ratio of height of a thermoelectric branch to its cross-section area decreases, failure rate of a single-stage TED reduces, and therefore failure-free operation probability increases.